Relaxation dynamics of 3He and 4He clusters and droplets studied using near infrared and visible fluorescence excitation spectroscopy. Issue 3 (21st December 2022) - von Haeften, Klaus; Laarmann, Tim; Wabnitz, Hubertus; Möller, Thomas
Abstract : The relaxation dynamics of electronically excited 3 He and 4 He clusters and droplets is investigated using time-correlated near-infrared and visible (NIR/VIS) fluorescence excitation spectroscopy. Abstract : The relaxation dynamics of electronically excited 3 He and 4 He clusters and droplets is investigated using time-correlated near-infrared and visible (NIR/VIS) fluorescence excitation spectroscopy. A rich data set spanning a wide range of cluster and droplet sizes is produced. The spectral features broadly follow the vacuum ultraviolet excitation (VUV) spectra. However, when the NIR/VIS spectra are normalised to the VUV fluorescence, regions with distinctly different cluster size and isotope dependence are identified, enabling deeper insight into the relaxation mechanism. Particle density, location of atomic-like states and their principal quantum number, n, are found to play an important role in the relaxation. For states with n = 3 and higher, only energy within the surface region is transferred to excited atoms which are subsequently ejected from the surface and fluoresce in vacuum. For states with n = 2, energy from the entire region within clusters and droplets is transferred to the surface, leading to the ejection of excited atoms and excimers. Here, the energy is transferred by excitation hopping, which competes with radiative and non-radiative decay, making ejection and NIR/VIS fluorescence inefficient in increasingly larger droplets.